2016
DOI: 10.1371/journal.pone.0148659
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Tumor Cells Identify Early Recurrence in Patients with Non-Small Cell Lung Cancer Undergoing Radical Resection

Abstract: BackgroundSurgery is the treatment of choice for patients with non-small cell lung cancer (NSCLC) stages I-IIIA. However, more than 20% of these patients develop recurrence and die due to their disease. The release of tumor cells into peripheral blood (CTCs) is one of the main causes of recurrence of cancer. The objectives of this study are to identify the prognostic value of the presence and characterization of CTCs in peripheral blood in patients undergoing radical resection for NSCLC.Patients and Methods56 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(80 citation statements)
references
References 23 publications
3
75
0
2
Order By: Relevance
“…Furthermore, liquid biopsy, e.g., CTC detection has been introduced and a few pilot studies regarding early diagnosis of lung cancer have been published [4765]. According to application in specific location and situation, we systemic reviewed clinical updates of these approaches focusing on development trends, detection rate and complications .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, liquid biopsy, e.g., CTC detection has been introduced and a few pilot studies regarding early diagnosis of lung cancer have been published [4765]. According to application in specific location and situation, we systemic reviewed clinical updates of these approaches focusing on development trends, detection rate and complications .…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the decrease or disappearance of CTCs following surgery has been correlated with improved clinical outcomes (28,29). A recent study (30) has prospectively analysed the kinetics of CTCs in blood samples of 56 patients obtained before surgery and one month after. The results showed that the presence of CTCs after surgery was significantly associated with early recurrence (P=0.018) and a shorter disease-free survival (DFS) (P=0.008).…”
Section: Ctcsmentioning
confidence: 99%
“…In early-stage patients, the decrease or disappearance of CTCs after surgery has been reported to correlate with better clinical outcomes (98, 99), while its persistence was associated with shorter progression-free survival (PFS) (100). Regarding advanced NSCLC, some studies have reported that a higher CTC count at presentation correlates with advanced stage and shorter PFS and overall survival (85, 101).…”
Section: Circulating Tumor Cellsmentioning
confidence: 99%